Making Livelihoods and Social Protection Gender-Sensitive - World Bank (Washington, DC, 2014)
This note on making livelihoods and social protection approaches gender- sensitive is the seventh in a series of guidance notes on gender issues in disaster risk management (DRM) in the East Asia and the Pacific region. Targeting World Bank staff, clients and development partners, this note gives an overview of the main reasons for including gender sensitive social protection and livelihoods approaches in DRM; it identifies the key challenges, and recommends strategies and tools for incorporating gender-sensitive social protection and livelihoods into DRM programs and strengthening the linkages between these disciplines.